2019
DOI: 10.1159/000495663
|View full text |Cite
|
Sign up to set email alerts
|

Gambling on Smartphones: A Study of a Potentially Addictive Behaviour in a Naturalistic Setting

Abstract: Smartphone users engage extensively with their devices, on an intermittent basis for short periods of time. These patterns of behaviour have the potential to make mobile gambling especially perseverative. This paper reports the first empirical study of mobile gambling in which a simulated gambling app was used to measure gambling behaviour in phases of acquisition and extinction. We found that participants showed considerable perseverance in the face of continued losses that were linearly related to their prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(50 reference statements)
0
10
1
Order By: Relevance
“…Gaming is a fairly frequent activity among students [ 41 ], especially among men, but women have joined this activity mainly because the smartphone is the logic platform for casual games (designed for accessibility, simplicity and the speed with which rules can be grasped), such as ‘Candy Crush’ or ‘Pou’ and unlike games such as ‘League of Legends’ and ‘World of Warcraft’, whose most suitable game platform is the personal computer. However, contrary to expectations [ 42 , 43 ], gambling has not been recognised by users or by Past Usage as a frequent activity; once again, the high proportion of women in the sample could be the explanatory factor for this phenomenon. Significant gender differences were found between all uses except for online purchases, viewing of TV series, movies or videos, and organisational tasks.…”
Section: Discussioncontrasting
confidence: 95%
“…Gaming is a fairly frequent activity among students [ 41 ], especially among men, but women have joined this activity mainly because the smartphone is the logic platform for casual games (designed for accessibility, simplicity and the speed with which rules can be grasped), such as ‘Candy Crush’ or ‘Pou’ and unlike games such as ‘League of Legends’ and ‘World of Warcraft’, whose most suitable game platform is the personal computer. However, contrary to expectations [ 42 , 43 ], gambling has not been recognised by users or by Past Usage as a frequent activity; once again, the high proportion of women in the sample could be the explanatory factor for this phenomenon. Significant gender differences were found between all uses except for online purchases, viewing of TV series, movies or videos, and organisational tasks.…”
Section: Discussioncontrasting
confidence: 95%
“…We should mention that problematic smartphone use has been associated with specific behavioral addictions like gambling. A recent study indicated that gambling apps on smartphone can cause perseverative gambling behavior [28]. However, in our study we did not collect data on the type of activity on smartphones, which is a limitation for inferring results.…”
Section: Discussionmentioning
confidence: 93%
“…Some of these similarities are tied to the novel ways in which both gamblers and investors can make their decisions. Gambling on smartphones is considered by some gambling researchers to be particularly harmful, given its accessibility and potential speed of play (James et al, 2017(James et al, , 2019). Meanwhile, a new breed of smartphone investing apps are encouraging investors to check their portfolio frequently, trade aggressively, and even use sophisticated products such as options and leverage (Stewart, E., 2020).…”
Section: Introductionmentioning
confidence: 99%